Study on the Effect of Vitamin C Intake on the Serum Glutamic Pyruvic Transaminase (SGPT) Activity in Man - YOSHIMURA, Takeshi; TANADA, Seiki; IMAKI, Masahide; MATSUMOTO, Kazuoki; SEI, Masako; MIYOSHI, Tamotus (Japanese Journal of Health and Human Ecology, 1988)
The effect of the vitamicn C intake on serum SGPT activity was examined. The results are as follows. 1) In an epidemiological study, significant correlaiton was found between SGPT activity and serum vitamin C in 76 healthy young volunteers (y=-18.7x + 19.2, r=-0.383). 2) In a laboratory study, we administered vitamin C at dose of 1 g/day for 10 days and then at a dose of 10 g/day for 10 days to five subjects, but found not significant different between SGPT activity before and after treatment. 3) We administered vitamin C at dose of 1 g/day for 1 year, but found not significant different between SGPT activity before and after treatment.